Analysis of Public Satisfaction Levels in Gelora Bung Karno (GBK) City Forest Based on Socio-Cultural Functions - Ramadhania, Siti Chadijah Destiyanti; Pramono, Sidik (Jayapangus Press, 2024)
The Jakarta City Government, along with the central government, has implemented various measures to address the issue of air pollution that has become a serious problem for the city. One of the efforts undertaken is to increase the provision of urban green spaces and restore the function of the GBK City Forest as a public green open space (GOS). However, there has been no research showing the public's perspective and satisfaction with the utilization of the GBK City Forest. This study aims to determine the level of public satisfaction with the GBK City Forest based on social-cultural functions. The assessment indicators used to measure public satisfaction in this study are based on the theory of cultural ecosystem services developed by Shijie Gai et al. The data used in this study were obtained using mixed methods data collection techniques through questionnaires (quantitative) as well as in-depth interviews and literature studies (qualitative). Based on the results of the study, it can be concluded that the majority of the public is highly satisfied with the utilization of the social-cultural functions of the GBK City Forest. However, some people still complain about the lack of supporting facilities for recreational activities and the disturbances from external parties that make them feel uncomfortable when engaging in activities at the GBK City Forest. Therefore, it is important for the government and the GBK City Forest management to consider public feedback and improve the quality and safety of the existing facilities.